2022
DOI: 10.1063/5.0063797
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of pressure pulsation in vertical submersible axial flow pump device under bidirectional operation

Abstract: In order to analyze the pressure pulsation characteristics of a single-conduit vertical submersible axial-flow pump device under bidirectional operation, the unsteady numerical simulation of the pump device was carried out based on computational fluid dynamics. The pressure pulsation coefficient and fast Fourier transform were used to analyze the pulsation of each monitoring point in the time–frequency domain. The results show that the pressure pulsation at different positions of the pump device is mainly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In order to clarify the force variation of the impeller in the calculation condition, the axial force (F Z ) and radial force (F R ) of the impeller are calculated (Yang et al, 2022b). The calculation formulas of axial force and radial force are as follows:…”
Section: Unsteady Flow Characteristics In the Impellermentioning
confidence: 99%
“…In order to clarify the force variation of the impeller in the calculation condition, the axial force (F Z ) and radial force (F R ) of the impeller are calculated (Yang et al, 2022b). The calculation formulas of axial force and radial force are as follows:…”
Section: Unsteady Flow Characteristics In the Impellermentioning
confidence: 99%
“…The instantaneous pressure must be dimensionless in the time domain analysis process to remove static pressure disturbance. The pulsating pressure coefficient ( C p ) was used by references 42,50 to analyze time series data. The C p was calculated statistically on all grids inside the turbine’s flow domain to aid in the identification of places with exceptionally unsteady flows.…”
Section: Numerical and Experimental Frameworkmentioning
confidence: 99%
“…Recently, with the rapid growth of meshing techniques [8], numerical algorithms [9], and post-processing methods [10], the investigation of the internal pressure pulsation of axial-flow pumps based on computational fluid dynamics (CFD) has made remarkable progress [11,12]. Yang et al [13] found that rotor-stator interference between the impeller and guide vanes is one of the most important inductors for strong pressure pulsation inside the axial-flow pump.…”
Section: Introductionmentioning
confidence: 99%